Postpartum Exercise among Nigerian Women: Issues Relating to Exercise Performance and Self-Efficacy. (15th June 2013) - Adeniyi, A. F.; Ogwumike, O. O.; Bamikefa, T. R.
Abstract : Physical exercise during postpartum period is beneficial to mothers, and the health gains are abundantly reported. This study characterises the postpartum exercise profile of a group of Nigerian women and reports how their exercise self-efficacies are influenced by sociodemographic characteristics. Participants were women attending the two largest postnatal clinics in Ibadan, south-western Nigeria. A self-developed questionnaire assessed the socio-demographic and exercise profile of participants, while the Exercise Self-Efficacy Scale assessed their exercise self-efficacy. About two-third (61.0%) of the participants were not aware that they could undertake physical exercise to enhance postpartum health, and 109 (47.8%) were not engaged in any exercise. Those who exercised did so for less than three days/week, and 89% of the women did not belong to any exercise support group. Exercise self-efficacy was significantly (P < 0.05 ) associated with being in an exercise programme, age, employment, work hours/week, monthly income, and number of pregnancies. Most of the women were not aware they could engage in postpartum exercise, and about half were not undertaking it. More women with high compared to moderate exercise self-efficacy undertook the exercise. Efforts at increasing awareness, improving exercise self-efficacy and adoption of postpartum exercise are desirable among the Nigerian women.